A model‐based approach to analyze the influence of UGT2B15 polymorphism driven pharmacokinetic differences on the pharmacodynamic response of the PPAR agonist sipoglitazar. (20th November 2013) - Stringer, Frances; DeJongh, Joost; Scott, Graham; Danhof, Meindert
Abstract The pharmacokinetics of sipoglitazar, a peroxisome proliferator activated receptor agonist, are subject to high inter‐individual variability resulting from a polymorphism of the UGT2B15 genotype. The aim of the current analysis was to apply a PK–PD model‐based approach to evaluate the influence of UGT2B15 driven pharmacokinetic differences on the clinical response. Efficacy and safety of sipoglitazar compared to placebo were assessed in Type 2 Diabetes Mellitus patients in two Phase II randomized, double‐blind studies (sipoglitazar once daily: 8, 16, 32, or 64 mg; sipoglitazar twice daily: 16 or 32 mg; rosiglitazone 8 mg once daily and placebo for 13 weeks; n = 780). Changes in fasting plasma glucose (FPG) and glycosylated hemoglobin (HbA1c) levels over time were described as a function of individual drug exposure using a simultaneous, cascading indirect response model structure. The effects on FPG and HbA1c could successfully be described for placebo, rosiglitazone, and sipoglitazar treated groups in all three UGT2B15 genotypes. Differences in drug effects between genotypes were fully explained by differences in drug exposure. The current PK–PD analysis confirms that UGT2B15 genotype is a major determinant for differences in FPG and HbA1c response to sipoglitazar treatment between Type 2 Diabetes mellitus patients, due to related differences in drug exposure.